Electron impact ionisation cross section for organoplatinum compounds. (1st November 2016) - Mahato, Dibyendu; Naghma, Rahla; Alam, Mohammad Jane; Ahmad, Shabbir; Antony, Bobby
ABSTRACT: This article reports electron impact ionisation cross sections for platinum-based drugs viz., cisplatin (H6 N2 Cl2 Pt), carboplatin (C6 H12 N2 O4 Pt), oxaliplatin (C8 H14 N2 O4 Pt), nedaplatin (C2 H8 N2 O3 Pt) and satraplatin (C10 H22 ClN2 O4 Pt) complexes used in the cancer chemotherapy. The multi-scattering centre spherical complex optical potential formalism is used to obtain the inelastic cross section for these large molecules upon electron impact. The ionisation cross section is derived from the inelastic cross section employing complex scattering potential–ionisation contribution method. Comparison is made with previous results, where ever available and overall a reasonable agreement is observed. This is the first attempt to report total ionisation cross sections for nedaplatin and satraplatin complexes. Abstract :